ROLE OF PREBIOTICS IN CHILDREN'S DIET - A. I. Khavkin; O. N. Komarova ("Paediatrician" Publishers LLC, 2014)
Nourishment is a complex multicomponent process ensuring the majority of the vital needs of the organism. The connection between food components and immune response is generally admitted. This connection is especially important in different periods of childhood when intense formation of immune mechanisms is taken place. Microflora and prebiotics - nutrients which to a great extent maintain the normal function of the immune system play the key role in development and functioning of the immune component of the gastrointestinal tract where almost 2/3 of all immunocompetent cells are concentrated. It is particularly significant that prebiotics have multiple effects on the organism, modulating metabolic processes both mediately through the intestinal microflora and directly through immunocompetent cells. The understanding of necessity of prebiotics including into the children's diet and correction the daily ration according to this fact is the first step in treatment and prophylaxis of various disorders.